Influences of the input factors towards the success of an information system project - Subiyakto, A'ang; Ahlan, Abdul Rahman; Kartiwi, Mira; Sukmana, Husni Teja (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2015)
This study tried out three input factors which theoretically affect the success of information system (IS) project. These factors were adopted from the McLeod and MacDonell’s (M&M’s) project framework and then examined using survey toward the internal project stakeholder in a sampled institution. A stratified sampling was carried out based on the project experience ownership and then sent both online and paper-based questionnaires to 130 selected respondents. A number of 62 (48%) valid responses were analysed using a partial least squares-structural equation modelling (PLS-SEM) software. The significances of path coefficients, the acceptances of hypotheses, the predictors relevances, and the moderate coefficient determination of the IS project’s success variable present the proposed model approval for the subsequent studies.